Changes in public support for alcohol policies in NSW, Australia, 2013-2019 - Wendy L Watson; Natalie Stapleton; Penny Buykx; Clare Hughes; Anita Dessaix (Sax Institute, 2022)
Objectives: Alcohol contributes to significant health, social and economic burdens worldwide, but evidence-based policy options can reduce the harm associated with alcohol use. The aim of this paper is to understand factors influencing public support for various alcohol policies in New South Wales (NSW), Australia, and to determine any change over time. Methods: An online survey of adults in NSW, in 2013 (n = 2482), 2016 (n = 1585) and 2019 (n = 1601), assessed support for alcohol policies. Multivariable logistic regression models examined the change in support over time, adjusting for demographics, alcohol consumption, smoking status and knowledge of alcohol as a risk factor for cancer. Results: Most participants (68-72%) supported policies preventing underage internet users from exposure to alcohol advertising, and banning alcohol sponsorship of underage music and sporting events. Fiscal policies and restrictions on the number of alcohol outlets were the least supported policies (<40% support). Compared with 2013, participants in 2016 and 2019 were less likely to support policies increasing price, applying a volumetric tax and reducing the number of alcohol outlets. In 2019, more than 55% of respondents were aware that alcohol was a cancer risk factor, and knowledge of that relationship was associated with an increased likelihood of support for alcohol policies. Conclusions: Support was greatest for alcohol harm-reduction policies that had less impact on an individual's drinking. Overall, support for alcohol policies in NSW is not increasing. Initiatives to raise awareness about the health consequences of alcohol use, together with effective alcohol policies, are needed to counter industry influence on decision makers and negative public discourse.